CT-guided fine-needle aspiration of abdominal and retroperitoneal small lesions with the coaxial technique using MPR images - De Filippo, Massimo; Saba, Luca; Azzali, Emanuele; Milanese, Gianluca; Mostardi, Maurizio; Borgia, Daniele; Capasso, Raffaella; Nizzoli, Rita (Acta Biomedica Atenei Parmensis, 2016)
Purpose: To demonstrate the advantages of CT-guided fine-needle aspiration (FNA) of abdominal and retroperitoneal small lesions with the coaxial technique using MPR images. Materials and methods: The study included retrospectively 50 patients who underwent CT-guided FNA of abdominal and/or retroperitoneal small lesion (<30 mm). Patients with suspected lymphomas or sarcomas were excluded. Cytology reports were the reference standard. Results: The cytology was diagnostic in 48/50 biopsies (96%): out of 41 neoplastic lesions (85%), 37 were malignant (90.2%) and 4 were benign (9.8%); 7 out of 48 were non-neoplastic (14.6%). No procedural complications were observed (0%). Conclusion: By using MPR images there is an effective improvement in coaxial CT-guided FNA of abdominal and retroperitoneal small lesions.